2023
DOI: 10.3846/tede.2023.18536
|View full text |Cite
|
Sign up to set email alerts
|

Regional Disparities as a Result of Differences in Human Capital and Innovativeness on the Example of Poland

Abstract: Inequalities in human capital most often affect other spheres of life. It is people who create innovation, so the unequal distribution of human capital and innovation in the regions leads to development disparities between regions. This, in turn, is a force inhibiting the achievement of higher levels of prosperity at the national level. The existing studies mainly focus on the assessment of disparities in development between countries. Although understandings of mechanisms of regional disparities, i.e., assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…In the case of Finland and Sweden over the 1987-2015 period, Eliasson et al (2021) revealed statistically insignificant changes in the geographical dispersion of human capital on the inter-regional scale, large and persistent disparities between the core and hinterlands, and the largest intra-regional differences within the metropolitan labour markets. Jagódka and Snarska (2023) found human capital to be the main driver of regional disparities in Polish NUTS 2 regions and investigated whether it was fully utilised in creating innovations.…”
Section: Research Backgroundmentioning
confidence: 99%
“…In the case of Finland and Sweden over the 1987-2015 period, Eliasson et al (2021) revealed statistically insignificant changes in the geographical dispersion of human capital on the inter-regional scale, large and persistent disparities between the core and hinterlands, and the largest intra-regional differences within the metropolitan labour markets. Jagódka and Snarska (2023) found human capital to be the main driver of regional disparities in Polish NUTS 2 regions and investigated whether it was fully utilised in creating innovations.…”
Section: Research Backgroundmentioning
confidence: 99%